Mengevaluasi Kesiapan Penerapan Sistem Digitalisasi Lembang Bo'ne Buntu Sisong - Binti Kisman, Rizky; Waliyuddin; Didi Eza Rizaldy; Ahmad Kamil Makarim; Sahrani; Dian Resky Pangestu; Musmulyadi (Makkareso: Riset Pengabdian Masyarakat, 2023)
Advances in digital technology are currently expected to support service programs to the community in Indonesia, one of which is through a website that has adopted a digitization system with the development of the Lembang Bo'ne Buntu Sisong website. Its application in Lembang Bo'ne Buntu Sisong, there are still several evaluations that need to be done because the target in understanding and using the digitalization system has not been fully achieved. The purpose of this activity is to explore and evaluate the readiness of the implementation of the digitization system at Lembang Bo'ne Buntu Sisong. The service method used is the Asset Based Community Development (ABCD) method. The results of the service showed that the implementation of the digitization system in Lembang Bo'ne Buntu Sisong was successfully developed with the Lembang government as an effort to improve information and administrative services. Several evaluations in its development such as: human resources to review the success of human resources in maintaining the continuity of website performance; infrastructure and internet access. The benefit of this service is the presence of a digitalization policy carried out in Lembang Bo'ne Buntu Sisong to facilitate digital-based citizen services. It also adds to the experience of students to increase competence and concern for changes in their social environment and build collaboration with the community